2019
DOI: 10.1111/csp2.82
|View full text |Cite
|
Sign up to set email alerts
|

Myth debunked: Keratinous pangolin scales do not contain the analgesic tramadol

Abstract: Conservation plans aiming to reduce the threat of illegal wildlife trade increasingly recognize the need for multifaceted approaches that include both enhanced enforcement and demand reduction initiatives. Both are complex issues that involve understanding consumer motives. Pangolins represent some of the most heavily trafficked species, largely due to high consumer demand for their scales for use in traditional medicines. Recent media reports also suggest that demand is related to the purported presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Chemometric analysis with the Mass Mountaineer software has been widely applied for plant chemotaxonomy 65 – 75 and animal chemotaxonomy 76 , 77 . Musah and coworkers used these chemometric methods for speciation of necrophagous insect eggs based upon amino acid profiles 78 , and also for species-level identification of fly larvae feeding on decomposing remains 79 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemometric analysis with the Mass Mountaineer software has been widely applied for plant chemotaxonomy 65 – 75 and animal chemotaxonomy 76 , 77 . Musah and coworkers used these chemometric methods for speciation of necrophagous insect eggs based upon amino acid profiles 78 , and also for species-level identification of fly larvae feeding on decomposing remains 79 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, many Sinularia species produce secondary metabolites used for allelopathy and predator deterrence, , making the genus a rich and diverse source of bioactive natural products . These molecules serve as biomarkers for the respective species in which they are found, and their discovery hints at the possibility that there may be genus- and species-specific chemical profiles that have the potential to serve as a tool that can be used for genus and species identification and differentiation. Such metabolome profiles have been shown to be correlated to species identity and/or can be used for genus and even species-level classification of endangered wildlife, including pangolins and Brazilian redwoods, necrophagous insects, and psychoactive plants . This approach involves the generation of metabolome profiles by a spectroscopic or mass spectrometric technique, the outputs of which are processed by multivariate statistical analysis to generate prediction models against which unknown samples can be screened to glean genus- or species-level information .…”
Section: Introductionmentioning
confidence: 99%
“…Because the analysis is commonly performed under soft ionization conditions, the output of a typical analysis is a mass spectrum with peaks representative of the unfragmented protonated precursors of all of the molecules that are detected. The range of compounds spans the dielectric constant spectrum and, for the analysis of complex unprocessed matrices in particular, has been shown to yield species-specific chemical profiles that can serve as the basis for prediction of species identity. Importantly, each analysis takes ∼5 s, and thus, the hundreds or thousands of sample replicates required to create species-specific databases against which unknown samples can be screened to learn of their species identity can be rapidly created. Thus, while it would be ideal to be able to utilize DNA barcoding approaches for genus identification, alternative methods that can accomplish this task more rapidly and in the short term would be of value.…”
Section: Introductionmentioning
confidence: 99%
“…Pablo Escobar loved animals, in particular birds, explained his brother Roberto Escobar during an interview at his villa. He sought expert advice on which species could survive in this location and used military transport planes after opening hours to land the animals at the airport of Medellín.4 See alsoJacobs et al (2019) 'Myth debunked: Keratinous pangolin scales do not contain the analgesic tramadol'. (The reason for this combination of contraband is unclear although rumours were reported that pangolin scales were being used as a drug substitute for methamphetamine, and also that drug networks have adopted this new commodity into their portfolio).…”
mentioning
confidence: 99%
“… 4 See also Jacobs et al ( 2019 ) ‘Myth debunked: Keratinous pangolin scales do not contain the analgesic tramadol’. (The reason for this combination of contraband is unclear although rumours were reported that pangolin scales were being used as a drug substitute for methamphetamine, and also that drug networks have adopted this new commodity into their portfolio).…”
mentioning
confidence: 99%